Contributaries. From confusion to confluence in the matter of water and agency. (26th November 2014) - Strang, Veronica
Abstract : I am happy to see that my essay has generated a lively discussion, and am most grateful to the respondents for their insightful contributions. Their comments express varying levels of agreement regarding the agency of things. Vernon Scarborough revisits anxieties about whether agency implies intentionality. Using the term 'agency' is indeed problematic if we assume that it entails sentience or intentionality (and I do not), but if we define it more precisely as a capacity to act (upon), it is possible to excise intentionality from the equation. This simultaneously allows us to acknowledge the agentive capacities of things without proposing or implying a form of faux animism. Anthropology has indeed drawn imaginatively on specifically cultural beliefs and knowledges, for example in composing more relational visions of human–other interactions than Western science tends to allow (see Strang2006a ), but this is not tantamount to assuming that things contain spiritual presence, or have 'their own sense of agency'.